The Confederation Group of Canadian poets, 1880-1897 - Bentley, D. M. R. (University of Toronto Press, 2004)
"As one of the formative periods in Canadian history, the late nineteenth century witnessed the birth of a nation, a people, and a literature. In this study of Canada's first 'school' of poets, D.M.R. Bentley combines archival work, including extensive research in periodicals and newspapers, with close readings of the work of Charles G.D. Roberts, Archibald Lampman, Bliss Carman, William Wilfred Campbell, Duncan Campbell Scott, and Frederick George Scott. Bentley chronicles the formation, reception, national and international successes, and eventual disintegration (after the 1895 'War among the Poets') of the Confederation Group, whose poetry forever changed the perception and direction of Canadian literature." "With the aid of biographical, political, and sociological analyses, Bentley's literary history delineates the group's political, aesthetic, and thematic dispositions and characteristics, and contextualizes them not only within Canadian history and politics, but also within contemporary intellectual and literary currents, including Romantic nationalism, 'Canadianism, ' and poetic formalism. Bentley casts new light on the poets' commonalities - such as their debt to Young Ireland, their commitment to careful workmanship, and their participation in the American mind-cure movement - as well as on their most accomplished and anthologized poems from 1880 to 1897. In the process, he presents a compelling case for the literary and historical importance of these six men and their poems in light of Canada's cultural and political past, and defends their right to be known as Canada's first poetic fraternity at a time when Canada was striving to achieve literary and national distinction. The Confederation Group of Canadian Poets, 1880-1897 is an erudite and innovative work of literary history and critical interpretation that belongs on the bookshelf of every serious scholars of literary studies."--Jacket